Cylindrical intensive vs. double surface LED phototherapy for neonatal hyperbilirubinemia - Rini Sulviatni; Khonsa Hartsu Syuhada; Hanny Krissanti; Denny Purnama (Indonesian Pediatric Society, 2021)
Background High bilirubin levels may lead to complications such as bilirubin encephalopathy or even death. Therefore, neonatal hyperbilirubinemia patients require appropriate treatment in the form of phototherapy or exchange transfusion. With the advancement of technology, various types of phototherapy, such as the cylindrical intensive phototherapy (bilisphere) and double LED, are now available. Objective To compare cylindrical intensive phototherapy to double surface LED phototherapy in neonatal hyperbilirubinemia. Methods This cohort study was conducted in neonates with hyperbilirubinemia at at Syamsudin SH Hospital, Sukabumi, West Java, who were treated with either cylindrical intensive phototherapy or double surface LED phototherapy. The variables observed were subjects’ characteristics, bilirubin levels pre- and post-therapy, duration of phototherapy, length of stay, and total treatment cost. The data were analyzed using univariate and bivariate analyses. Results Of 47 neonates, the mean bilirubin levels were 19.36 mg/dL pre-therapy and 12.26 mg/dL post-therapy. Subjects’ overall mean duration of phototherapy was 24 hours, mean length of stay was 1 day, and mean cost of treatment was IDR 813,175. There was no significant difference in the bilirubin decrease between the cylindrical intensive phototherapy and double LED groups. However, there were significant differences between the cylindrical intensive phototherapy and double LED groups in duration of phototherapy (10.75 vs. 75.17 hours, respectively (P<0.000), mean length of stay (1 vs. 3.13 days, respectively (P<0.000), and total cost of treatment (IDR 598,918 vs. IDR 1,036,747, respectively P<0.000). Conclusion While the decrease in bilirubin was not significantly different in neonatal hyperbilirubinemia patients who underwent cylindrical intensive phototherapy compared to double LED therapy, cylindrical intensive phototherapy relates to significant shorter phototherapy duration, length of stay, and total treatment cost. Hence, cylindrical intensive phototherapy phototherapy is considered to be more time-efficient and cost-efficient than double LED phototherapy.